Perkembangan penelitian bidang manajemen pengetahuan di Indonesia berdasarkan perspektif bibliometrik dengan basis aplikasi VOSViewer - Maula Siti Sarah; Yunus Winoto (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
This article aims to examine the development of the field of knowledge management by analyzing the number of publications in the Google Scholar database with the keyword knowledge management in the last 10 years starting from 2012-2021. This bibliometric analysis uses co-word analysis with the help of VOSViewer software. The results showed that there were 770 publications in this field in the period 2012-2021 where this number continued to decrease from year to year. Based on the results of mapping using VOSViewer, knowledge management systems and knowledge sharing were the two areas that were most researched during that period, especially in 2012-2013. Meanwhile, fields related to big data, organizational performance and other related fields that are still within the scope of knowledge management have only emerged a few years ago and are still lacking in research. This is certainly an opportunity for future researchers who wish to conduct research in this field.